2013
DOI: 10.1159/000353872
|View full text |Cite
|
Sign up to set email alerts
|

Staining Properties of Brilliant Blue Depending on Different Incubation Times and Solvents in Humans

Abstract: Purpose: Intravitreous injection of vital dyes, e.g. brilliant blue (BBG), promotes better visualization of the internal limiting membrane (ILM). This paper investigates the staining properties of BBG depending on different incubation times and 2 types of solvents - 5% glucose (GL) or saline solution - in a prospective study in patients. Methods: This paper investigates various aspects of BBG in various methods. An interventional prospective study was conducted in patients to examine the binding properties of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…We standardised the technique of staining between the two dyes and importantly used the same contact time between the dyes and retina, before washout. Both dyes showed selective ILM staining at this duration with low affinity for epiretinal membrane (ERM) as previously described for BBG, [22] and allowing the presence of epiretinal tissue on the ILM to be detected by negative staining as we have previously described for BBG [11]. This is a useful tool during surgery, allowing areas of bare ILM to be identified, but we were also careful to avoid areas of negative staining when making the contrast measurements by using areas of maximum stain around the peeled area as others have done [23].…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…We standardised the technique of staining between the two dyes and importantly used the same contact time between the dyes and retina, before washout. Both dyes showed selective ILM staining at this duration with low affinity for epiretinal membrane (ERM) as previously described for BBG, [22] and allowing the presence of epiretinal tissue on the ILM to be detected by negative staining as we have previously described for BBG [11]. This is a useful tool during surgery, allowing areas of bare ILM to be identified, but we were also careful to avoid areas of negative staining when making the contrast measurements by using areas of maximum stain around the peeled area as others have done [23].…”
Section: Discussionsupporting
confidence: 56%
“…Importantly the two groups were well matched in terms of the amount of vitreous debris present on the ILM, which, if unequal between the two groups, could have confounded contrast measurements. It is possible that AV17 may require a longer time for optimum ILM staining than BBG although contact time was found to have a limited effect on staining intensity with BBG in previous studies [22].…”
Section: Discussionmentioning
confidence: 87%
“…Rodrigues et al 24 and Hernandez et al 25 However, this study was done on the in vitro porcine retinas and the results may not be comparable to the situation in the human retina clinically. In other words, the dyes staining capability may differ from species to species.…”
Section: Staining Visibility Testmentioning
confidence: 86%
“…BBG performs a selective ILM staining with a low affinity for ERM [4,22]. This is important because the visualization and removal of the ILM is challenging as the structure is about 1 µm thick and is formed by the end feet of Müller cells and astrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation of Januschowski et al for the improved biocompatibility of ILM Blue could be that the dye solutions sold by a manufacturer place special emphasis on the purity of the ingredients and quality control [3]. It could also be argued that the presence of 4% PEG has a potential neuroprotective effect [22]. In particular, potential toxicity is a decisive factor in the choice of the vital dye and is part of the current research, as the currently used vital dyes have shown retinal toxic reactions [5,[9][10][11]18,19].…”
Section: Discussionmentioning
confidence: 99%